2006
DOI: 10.1097/00001199-200605000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Complicated Mild Traumatic Brain Injury on the Inpatient Rehabilitation Unit

Abstract: Despite favorable GCS scores, some patients with CMTBI suffer a variety of serious cranial and noncranial complications. Such patients appear to benefit from additional brain injury services offered in inpatient rehabilitation. Further study of the unique treatment needs of these patients is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
1
23
1
Order By: Relevance
“…Twelve percent of these patients had contusions and intracranial haemorrhage and 10% suffered skull fractures. These results support previous international findings [14,16] . Williams et al [14] found that persons with GCS scores of 13-15, and positive findings on a CT scan, had a course of recovery similar to that of persons with moderate TBI, but a worse outcome compared to those with similar GCS scores without CT findings.…”
Section: Severity Of Tbisupporting
confidence: 93%
See 1 more Smart Citation
“…Twelve percent of these patients had contusions and intracranial haemorrhage and 10% suffered skull fractures. These results support previous international findings [14,16] . Williams et al [14] found that persons with GCS scores of 13-15, and positive findings on a CT scan, had a course of recovery similar to that of persons with moderate TBI, but a worse outcome compared to those with similar GCS scores without CT findings.…”
Section: Severity Of Tbisupporting
confidence: 93%
“…Mild TBI accounts for 80-90% of all head injuries, according to international studies [1,8,11,13] . Some studies have shown that approximately 10-17% of in-patient admissions with initial mild TBI severity, as measured by the Glasgow Coma Scale (GCS), had intracranial lesions and that large numbers of these patients need rehabilitation after discharge from the acute hospital [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, individuals whose Glasgow Coma Scale (GCS) scores are in the generally accepted 'mild' range (i.e., 13-15) and who also demonstrate abnormalities on conventional neuroimaging are described using the term 'complicated mTBI' and their recoveries are more similar to those with GCS-defined moderate, rather than uncomplicated mild, TBI (Borgaro et al, 2003;Iverson, 2006a;Kashluba et al, 2008;Kennedy et al, 2006;Lange et al, 2009;van der Naalt et al, 1999;Williams et al, 1990). Individual difference in neurogenetics relevant to neural repair, neural plasticity, and neurotransmitter function also may influence outcome after mTBI (Arciniegas et al, 2003;Jordan, 2007;McAllister, 2009).…”
Section: Persistent Postconcussive Symptomsmentioning
confidence: 99%
“…For example, a linear relationship with cerebral atrophy relates to injury severity measures such as GCS, PTA, and duration of LOC Wilde et al, 2006b). Likewise, complicated mTBI is more likely to have positive neuroimaging findings (Levine et al, 2006;McAllister et al, 2001;Vorst et al, 2007) and significant residuals (Kennedy et al, 2006). If boxing is considered a model for detecting "pre-clinical" or asymptomatic brain injury, recent diffusion tensor imaging studies have demonstrated abnormalities in boxers (Chappell et al, 2006;Zhang et al, 2006b).…”
Section: Is Brain Injury On a Continuum: Concussion R Severe Tbi?mentioning
confidence: 99%